2020
DOI: 10.1108/lodj-10-2019-0433
|View full text |Cite
|
Sign up to set email alerts
|

The effect of authentic leadership and psychological capital on work engagement: the mediating role of job satisfaction

Abstract: PurposeThis study aims to investigate the effect of authentic leadership and psychological capital (PsyCap) on work engagement via job satisfaction by employing the job demands-resources (JD-R) model.Design/methodology/approachParticipants were 307 (52% male and 48% female) employees randomly recruited from a state-owned company in the eastern part of Indonesia. Most participants had completed an undergraduate degree with a mean age of 27.55 (SD = 7.89). The study employed a three-wave data collection techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 77 publications
6
43
1
Order By: Relevance
“…For instance, Woolley et al (2011) suggested that Authentic Leadership's contribution to a positive work climate was perceived as more influential by male than female employees. In contrast, Wirawan et al (2020) found that gender did not moderate Authentic Leadership's effect on Employees' Engagement. Hypothetically, women would need more support from leaders because they might experience a higher work-family conflict and role conflict while working from home (Cinamon & Rich, 2002;Grönlund, 2007).…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…For instance, Woolley et al (2011) suggested that Authentic Leadership's contribution to a positive work climate was perceived as more influential by male than female employees. In contrast, Wirawan et al (2020) found that gender did not moderate Authentic Leadership's effect on Employees' Engagement. Hypothetically, women would need more support from leaders because they might experience a higher work-family conflict and role conflict while working from home (Cinamon & Rich, 2002;Grönlund, 2007).…”
Section: Introductionmentioning
confidence: 58%
“…Woolley et al (2011) have postulated that male employees perceived Authentic Leadership more positively due to organizational values. However, in a more neutral organization (i.e., perceived gender equality), gender showed a non-significant moderating effect (Wirawan et al, 2020). While juggling with work and family demands, employees need support from leaders to secure their resources and maintain performance.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results indicated that there existed significant positive relationships between PsyCap with JS (β = 0.44, p < 0.01) and affective OC (β = 0.39, p < 0.01). In a similar vein, Wirawan et al (2020) found that the impact of PsyCap on an employee's JS was significant and positive, with a regression coefficient of (β = 0.32, p < 0.01). More literature in hospitality industry also proved that PsyCap was a predictive construct of job attitudes (e.g., Cheung et al, 2019;Viseu et al, 2020;Ribeiro et al, 2021).…”
Section: Hypotheses Development and Research Model Direct Effectsmentioning
confidence: 70%
“…Psychological Capital (PsyCap) is a form of employee's psychological resources (Luthans et al, 2015). To illustrate, PsyCap predicted engagement among front-line staff in the hospitality business (Paek et al, 2015), employees in various large for-profit companies (Chaurasia and Shukla, 2014;Joo et al, 2016;Wirawan et al, 2020), and public services (Saleh et al, 2020). Nevertheless, Kang & Busser (2018) and Parrott et al (2019) postulated that PsyCap and leadership should be employed to predict Work Engagement in different job types (e.g., technician vs. hospitality) and levels (e.g., staff vs. manager).…”
Section: Introductionmentioning
confidence: 99%